Bioimpressora 3D customizada para impressão de biotinta de nanocelulose e alginato carregada de células musculares - Patrícia Muniz de Oliveira (2023)
The increasing demand for tissue and organ transplants, the challenges and risks associated with autologous transplants, as well as the need for alternatives to obtain meat, fat, leather, and animal-free tissues, have driven significant scientific and industrial interest in biofabrication techniques. In recent years, extrusion-based 3D bioprinting has emerged as one of the most popular approaches for biofabrication. However, equipment and materials for the process still come at a high cost, which is a limitation for research applications. To overcome this issue, this work introduces an extrusion-based 3D bioprinter adapted from an existing conventional 3D printer. To transform it into a bioprinter, the plastic filament extruder system with the heating block was replaced by a mechanical extruder for hydrogels and bioinks, consisting of a piston driven by a screw. For prototype validation, CELLINK® Bioink loaded with C2C12 muscle cells was tested in a 3D bioprinting procedure. Experimental tests confirmed the viability of the process using the developed bioprinter and provided important insights into the morphology and proliferation of C2C12 muscle cells in bioinks composed of nanocellulose and alginate, with a noticeable increase in cell proliferation 14 days after bioprinting. Additionally, computational simulations were conducted to analyze the flow of inks and bioinks through the bioprinter’s extrusion nozzle and assess whether the generated shear stress compromises cell viability of the printed constructs.